2005
DOI: 10.4321/s0365-66912005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Lentes intraoculares con filtros para luz azul

Abstract: We obtained an improvement in favour of the tinted lens for all frequencies, with this being statistically significant at lower frequencies (3 and 6 cpd). No significant differences in the Farnsworth test performance or in the patient survey were found. The tinting provided by the IMPRUV filter brings an increase in contrast sensitivity without affecting colour perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, a large body of work shows no adverse outcomes with regard to visual acuity, 40-54 contrast sensitivity, 40-54 color vision, 40-54 or scotopic sensitivity. 43,[55][56][57] Although melatonin suppression may occur maximally from blue light, it is possible that a generalized increase in retinal illuminance in pseudophakic patients after cataract surgery outweighs any difference in blue-light transmission between the 2 types of IOLs. Alternatively, given that a relative increase in blue-light transmission can be seen postoperatively with both types of IOLs, a saturation effect for blue light-triggered melatonin suppression may occur whereby a partial blockade of blue light results in no clinical difference in sleep quality.…”
Section: Discussionmentioning
confidence: 96%
“…However, a large body of work shows no adverse outcomes with regard to visual acuity, 40-54 contrast sensitivity, 40-54 color vision, 40-54 or scotopic sensitivity. 43,[55][56][57] Although melatonin suppression may occur maximally from blue light, it is possible that a generalized increase in retinal illuminance in pseudophakic patients after cataract surgery outweighs any difference in blue-light transmission between the 2 types of IOLs. Alternatively, given that a relative increase in blue-light transmission can be seen postoperatively with both types of IOLs, a saturation effect for blue light-triggered melatonin suppression may occur whereby a partial blockade of blue light results in no clinical difference in sleep quality.…”
Section: Discussionmentioning
confidence: 96%
“…However, the AcrySof Natural IOL transmits a spectrum of visible light that mimics that of the natural human lens of a 53-year-old person without a cataract, and this similarity in the light-attenuating characteristics between the AcrySof Natural IOL and the human lens, particularly in the blue-light range (400 to 500 nm) has been observed. 9 Cristó bal et al 12 reported increased contrast sensitivity without affecting color perception in eyes with an AcrySof SN60AT IOL compared to eyes with an AcrySof SA60 IOL. The present 18-month clinical study comprising AcrySof SA60AT and AcrySof Natural SN60AT IOLs found similarity in postoperative recovery in terms of visual acuity, color perception, and contrast sensitivity in cataract patients with otherwise healthy eyes.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 Variable reports on the details of the optical performance of the IOL material and its impact on visual function are available. [4][5][6][7][8][9][10][11][12] The biomaterial of the AcrySof Natural and AcrySof IOLs (Alcon Laboratories) is impregnated with covalently bonded ultraviolet-absorbing chromophore. In addition, the AcrySof Natural IOL contains a covalently bonded chromophore that absorbs light in the 400 to 500 nm range.…”
mentioning
confidence: 99%